TRANSMITTING REFLECTIVE TEACHING PRACTICE INTO INDONESIAN EFL EDUCATORS’ PROFESSIONAL JOURNEYS - Kristian Florensio Wijaya (Widya Mandala Surabaya Catholic University, 2023)
It is principal to understand that EFL educators’ professional journeys are affected by varied internal and external factors such as school policies, particular curriculums, and educational cultures. From this stance, reflective teaching practice can act as one of the promising solutions to transfigure EFL educators into more well-rounded and thoughtful learning facilitators, which in turn is helpful to improve their entire teaching qualities. The researcher initiated this current small-scale qualitative library study to exhaustively investigate the influential impacts of transmitting reflective teaching practice into Indonesian EFL educators’ professional journeys. To fully attain this main study objective, the researcher employed a thematic analysis in reviewing the specifically-obtained research results derived from 25 reflective teaching studies. Based on the thematic analysis, it was deduced that through the constant internalization of reflective teaching practice, EFL educators can gradually transform into more professional language learning facilitators who are capable of promoting better-facilitated English learning enterprises.